HEALTH OF ELDERLY PRISONERS IN CLASS IIA BINJAI CORRECTIONAL INSTITUTION - Muhammad Bayu Refansyah; Mulyani Rahayu (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines the environmental factors affecting the health of elderly inmates at the Class IIA Correctional Institution in Binjai, recognizing that older prisoners represent a particularly vulnerable group within correctional settings. Using a descriptive qualitative approach with a case study design, data were collected through in-depth interviews, observations, and document analysis involving elderly inmates and health workers. The analysis follows the Miles and Huberman model, supported by NVivo software. The findings reveal that environmental conditions significantly influence the health of elderly inmates. Poor air circulation contributes to respiratory and skin disorders, limited access to clean water increases the risk of urinary tract infections, and inadequate sanitation leads to the spread of infectious diseases. Additionally, overcrowding exacerbates psychological stress and overall well-being. The study draws on Abraham Maslow’s theory of human needs and environmental stress concepts to highlight that unmet basic needs and stressful surroundings negatively impact health conditions. In conclusion, improving environmental quality within correctional facilities is essential to protect the health of elderly inmates. Systemic interventions are needed, including better sanitation, adequate water supply, improved ventilation, and more humane living conditions to support both physical and psychological well-being. Keywords: Elderly Prisoners; Health; Prison Environment; Basic Needs; Environmental Stress